"Songs of the Craft": Newsroom Work Poetry in Twentieth-Century American Journalism. Issue 4 (1st October 2020) - Mari, Will
ABSTRACT: Throughout the twentieth century, reporters and other news workers not only wrote about the news, they wrote about each other, their bosses, their daily grind in the newsroom, and journalism itself in the form of workplace poetry. This occupational verse was a way to relieve tension, vent about controlling editors and annoying readers. Writing the verses fulfilled a playful impulse and killed time between assignments. It helped to bond news workers with each other in the newsroom, and it allowed them to form their group identities in the face of difficult circumstances. This article briefly explores how occupational poetry, sometimes called "doggerel" by critics but even by its own creators, became part of the professionalization of American journalism and reflected changing newsroom values, priorities and a growing white-collar consciousness among news workers during and after the interwar years and during the early Cold War. Paradoxically, it echoed the blue-collar roots of many reporters, and their struggle and resistance. Ephemeral by nature, newsroom poetry survives into the present as an important commentary on the occupation.